MSMEs in the Architecture of Economic Governance: Analysis for Business Resilience and Worker Welfare in Bandar Lampung - Vincensius Soma Ferrer; Yulianto Yulianto (Journal of Research in Social Science and Humanities, 2026)
This research targets micro, small, and medium-sized enterprises (MSMEs) in the city of Bandar Lampung, Indonesia with operational resilience among MSMEs using a local economic governance system that relates to well-being employees as core issues. It uses an exploratory qualitative research design with thematic analysis; primary data collected included interviews of local practitioners that fulfilled the sample criteria were paired with secondary data from official documents, industry and governance reports as well as policy and regulatory literature. The research indicates that these businesses are more than small economic units — they support family income and facilitate the operation of the local economy as social spaces. Moreover, through the lens of public administration, this research describes economic governance as a bridge between central government administrative competence and economic behaviour, alongside recasting how MSME resilience is measured. The revised criteria require the measurements to go beyond the single requirement of business survival, and add new dimensions: retaining staff to stabilize employment and safeguarding employee well-being. Drawing on the legal authority granted to governments at all levels to support, protect, and empower MSMEs under  Government Regulation of the Republic of Indonesia No. 7 of 2021 and  and similar regulations at the local level, this study puts forward the policy proposition that governments must participate in strengthening local economic governance.